2015
DOI: 10.1039/c5ce00375j
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl linker effects on the coordination topology of ditopic di(2-pyridylmethyl)amine carboxylate ligands with ZnIIand CuII: polymersvs.macrocycles

Abstract: Di(2-pyridylmethyl)amine carboxylates with short alkyl linkers afford coordination polymers whereas the longer homologues favour macrocyclic topologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 74 publications
2
12
0
Order By: Relevance
“…This is in agreement with literature reports, as it has been noted for other, similar polymeric carboxylate-bridged Cu­(II) complexes that the polymeric complexes deaggregate into monomeric structures when in dilute solutions. If the polymeric structures would be retained in solution, isotropic EPR spectra would be expected, as observed for the bridged Cu­(II) carboxylate complexes reported with the ligands 3-((pyridin-2-ylmethylene)­amino)­propanoate and (6-amino-1,3-dimethyl-5­((2-carboxyphenyl)­azo)­uracil (when the solution spectrum was recorded in acetone; dissolving in DMSO resulted in a typical, axial Cu­(II) EPR spectrum showing deaggregation) . Since the monomeric forms of the complexes are relevant for our electrocatalytic experiments, we chose not to structurally characterize the other two Cu­(II) BEPA-carboxylate complexes, [Cu­(II)­(BEPA-Et)] + and [Cu­(II)­(BEPA-Bu)] + , as crystallization of these complexes as monomers seemed very unlikely, due to the fact that their BMPA analogues have already been shown to crystallize as coordination polymers. …”
Section: Results and Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with literature reports, as it has been noted for other, similar polymeric carboxylate-bridged Cu­(II) complexes that the polymeric complexes deaggregate into monomeric structures when in dilute solutions. If the polymeric structures would be retained in solution, isotropic EPR spectra would be expected, as observed for the bridged Cu­(II) carboxylate complexes reported with the ligands 3-((pyridin-2-ylmethylene)­amino)­propanoate and (6-amino-1,3-dimethyl-5­((2-carboxyphenyl)­azo)­uracil (when the solution spectrum was recorded in acetone; dissolving in DMSO resulted in a typical, axial Cu­(II) EPR spectrum showing deaggregation) . Since the monomeric forms of the complexes are relevant for our electrocatalytic experiments, we chose not to structurally characterize the other two Cu­(II) BEPA-carboxylate complexes, [Cu­(II)­(BEPA-Et)] + and [Cu­(II)­(BEPA-Bu)] + , as crystallization of these complexes as monomers seemed very unlikely, due to the fact that their BMPA analogues have already been shown to crystallize as coordination polymers. …”
Section: Results and Analysissupporting
confidence: 92%
“…As all of the BMPA-carboxylate ligands investigated here have already been characterized by X-ray diffraction as Cu­(II) complexes, we chose to crystallize one of the Cu­(II) BEPA-carboxylate complexes, as their structures have not yet been reported, so structural comparisons with the BMPA-carboxylate complexes can be made. For the previously reported complexes, it was found that ligands with carboxylate side chains of four (butylate) or more carbon atoms lead to the formation of linear, one-dimensional Cu­(II) coordination polymers in the solid state. , This has also been shown for [Cu­(II)­(BMPA-Et)] + and [Cu­(II)­(BMPA-Pr)] + when NO 3 – , BF 4 – , or ClO 4 – is used as the counterion. , We thus chose to crystallize [Cu­(II)­(BEPA-Pr)] + , using CuCl 2 as the Cu precursor, with the intention that the Cl – would have a stronger tendency to remain bound to the Cu­(II) ion and prevent the polymerization of the complexes. Along those lines, we have previously shown that [Fe­(BMPA-Pr)­(Cl)­(NO)] crystallizes as a monomer, whereas [Fe­(BMPA-Pr)­(NO)]­(ClO 4 ) forms a bridged metallacrown structure .…”
Section: Results and Analysismentioning
confidence: 99%
“…Seed crystal growth will proceed until the available monomer units in solution are consumed, and considering the 1:1 metal-ligand complex stoichiometry [9], and the excess of metal ions in solution, the CP, and therefore the NCP surfaces, likely terminate at a metal ion. This would lead to a high density of metal ions at the surface of the NCP.…”
Section: Discussionmentioning
confidence: 99%
“…6H 2 O was dissolved in water (2.0 mL) and carefully layered with a methanolic solution of C4COOH (0.100 mmol in 2.5 mL). Crystals suitable of C4COOH-CP for X-ray analysis were obtained within 2 days and were isolated, dried in air and weighed [9]. According to coordination topology of CP in Figure 1, three nitrogen atoms of C4COOH coordinate to one copper site, while the oxygen atoms of each carboxylate terminus coordinate unsymmetrically to an adjacent site, giving rise to the 1D coordination polymers.…”
Section: Coordination Polymer Of Cncoohmentioning
confidence: 99%
“…For the crystal structures of related copper(II) complexes with tetramethylethylen-1,2-diamine and carboxylate ligands; see: Ene et al (2009); Dorazco-Gonzá lez et al (2013); Liang et al (2004). For the synthesis of coordination compounds with onedimensional polymeric structures, see: Hong & You (2004); Colacio et al (2009); Rodpun et al (2015); Yang et al (2002). For their magnetic properties, see: Ene et al (2009); Kozlevčar et al (2004).…”
Section: Related Literaturementioning
confidence: 99%